A phase II trial of extended induction epratuzumab and rituximab for previously untreated follicular lymphoma: CALGB 50701 - Grant, Barbara W. (2013)
Rituximab combined with chemotherapy has improved the survival of previously untreated patients with follicular lymphoma (FL). Nevertheless, many patients neither want nor can tolerate chemotherapy, leading to interest in biological approaches. Epratuzumab is a humanized anti-CD22 monoclonal antibody with efficacy in relapsed FL. Since both rituximab and epratuzumab have single agent activity in FL, we evaluated the antibody combination as initial treatment of patients with FL. PATIENTS AND METHODS: Fifty-nine untreated patients with FL received epratuzumab 360 mg/m(2) with rituximab 375 mg/m(2) weekly for four induction doses. This combination was continued as extended induction in weeks 12, 20, 28, and 36. Response assessed by CT was correlated with clinical risk factors, FDG-PET findings at week 3, Fcg polymorphisms, immunohistochemical markers, and statin use. RESULTS: Therapy was well-tolerated with toxicities similar to expected with rituximab monotherapy. Fifty-two (88.2%) evaluable patients responded, including 25 complete responses (CR)(42.4%), and 27 partial responses (45.8%). At 3 years follow-up, 60% of patients remain in remission. Follicular Lymphoma International Prognostic Index (FLIPI) risk strongly predicted progression-free survival (p=0.022). CONCLUSIONS: The high response rate and prolonged time to progression observed with this antibody combination are comparable to those observed after standard chemo-immunotherapies and further support the development of biologic, non-chemotherapeutic approaches for these patients.